Unveiling the vulnerability of the human abducens nerve: insights from comparative cranial base anatomy in mammals and primates - Rotenstreich, Liat; Eran, Ayelet; Siegler, Yoav; Grossman, Rachel; Edery, Nir; Cohen, Roni; Marom, Assaf (Frontiers in Neuroanatomy, 2024)
The topographic anatomy of the abducens nerve has been the subject of research for more than 150 years. Although its vulnerability was initially attributed to its length, this hypothesis has largely lost prominence. Instead, attention has shifted toward its intricate anatomical relations along the cranial base. Contrary to the extensive anatomical and neurosurgical literature on abducens nerve anatomy in humans, its complex anatomy in other species has received less emphasis. The main question addressed here is why the human abducens nerve is predisposed to injury. Specifically, we aim to perform a comparative analysis of the basicranial pathway of the abducens nerve in mammals and primates. Our hypothesis links its vulnerability to cranial base flexion, particularly around the sphenooccipital synchondrosis. We examined the abducens nerve pathway in various mammals, including primates, humans (N = 40; 60% males; 40% females), and human fetuses (N = 5; 60% males; 40% females). The findings are presented at both the macroscopic and histological levels. To associate our findings with basicranial flexion, we measured the cranial base angles in the species included in this study and compared them to data in the available literature. Our findings show that the primitive state of the abducens nerve pathway follows a nearly flat (unflexed) cranial base from the pontomedullary sulcus to the superior orbital fissure. Only the gulfar segment, where the nerve passes through Dorello’s canal, demonstrates some degree of variation. We present evidence indicating that the derived state of the abducens pathway, which is most pronounced in humans from an early stage of development, is characterized by following the significantly more flexed basicranium. Overall, the present study elucidates the evolutionary basis for the vulnerability of the abducens nerve, especially within its gulfar and cavernous segments, which are situated at the main synchondroses between the anterior, middle, and posterior cranial fossae—a unique anatomical relation exclusive to the abducens nerve. The principal differences between the pathways of this nerve and those of other cranial nerves are discussed. The findings suggest that the highly flexed human cranial base plays a pivotal role in the intricate anatomical relations and resulting vulnerability of the abducens nerve.